2002
DOI: 10.1007/s00330-002-1720-8
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of women with breast cancer: comparison between MRI and FDG PET

Abstract: The aim of this study was to compare MRI of the breast with (18)F-fluoro-deoxy-glucose (FDG) positron emission tomography (PET) in patients with suspected local or regional breast cancer recurrence or suspected contralateral breast cancer. Thirty-two patients (mean age 57.2 years, age range 32-76 years) with suspected loco-regional recurrence ( n=19), chest wall recurrence ( n=5), and suspected secondary tumor of the contralateral breast ( n=8) underwent MRI of the breast and FDG PET of the whole body and brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(47 citation statements)
references
References 21 publications
1
42
0
4
Order By: Relevance
“…Breast MRI has been shown to be highly effective in identifying occult tumor, but FP findings may occur (6,(29)(30)(31)(32)(33)(34). As both MRI and PET/CT are frequently requested for disease evaluation for suspected breast cancer, a mechanism to foster direct comparison of lesions detected with both modalities would be useful (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast MRI has been shown to be highly effective in identifying occult tumor, but FP findings may occur (6,(29)(30)(31)(32)(33)(34). As both MRI and PET/CT are frequently requested for disease evaluation for suspected breast cancer, a mechanism to foster direct comparison of lesions detected with both modalities would be useful (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The breasts become markedly distorted when supine/prone images are registered and it is challenging to identify the corresponding lesion in all 3 orthogonal planes of the fused images (35). Several groups have suggested that an independent PET scan should be acquired in the prone position to increase the quality of PET in the breast (7,8,(36)(37)(38)(39)(40).…”
Section: Problems With Supine Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial experience with combined PET (functional imaging) and MRI (anatomical localization) has yielded positive results, providing benefits compared to either modality alone [12][13][14][15]. While no clinical scanners currently exist capable of acquiring images from both modalities, prototypes have been developed [16,17], and commercial devices are in the not too distant future.…”
Section: Introductionmentioning
confidence: 99%
“…Because the dosage unit of contrast media can't be translated, that is to say, the absolute difference on dosage among these studies is unknown, 2 articles were rejected. 17 studies (Fobben et al, 1995;Stomper et al, 1995;Fenlon et al, 1997;Helbich et al, 1997;Fischer et al, 1999;Alamo et al, 2001;Kawashima et al, 2001;Goerres et al, 2003;Knopp et al, 2003;Pediconi et al, 2005;Sardanelli et al, 2005;Kneeshaw et al, 2006;Pediconi et al, 2007;Pediconi et al, 2008;Woodhams et al, 2010;Luciani et al, 2011;Martincich et al, 2011) with 1934 patients were included based on the inclusion criteria and the data integrity.…”
Section: Literature Searchmentioning
confidence: 99%